2002
DOI: 10.1097/00007890-200202150-00025
|View full text |Cite
|
Sign up to set email alerts
|

Short Course Induction Immunosuppression With Thymoglobulin for Renal Transplant Recipients1

Abstract: Three-day induction with thymoglobulin is as effective and safe as seven days, decreases initial hospitalization and causes more sustained lymphocyte depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 8 publications
2
74
1
Order By: Relevance
“…These findings suggest that at lower-than-standard doses, RATG induction does not result in excess immunosuppression, even in combination with anti-IL-2R mAb. Our study was not powered to assess whether the low-dose regimen also could avoid the excess long-term risk for opportunistic infections, lymphoproliferative disorders, or malignancies associated with standard thymoglobulin-based induction regimens (41)(42)(43). On the basis of previous findings, however, patients who were exposed to less RATG were at lower risk (20).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that at lower-than-standard doses, RATG induction does not result in excess immunosuppression, even in combination with anti-IL-2R mAb. Our study was not powered to assess whether the low-dose regimen also could avoid the excess long-term risk for opportunistic infections, lymphoproliferative disorders, or malignancies associated with standard thymoglobulin-based induction regimens (41)(42)(43). On the basis of previous findings, however, patients who were exposed to less RATG were at lower risk (20).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, even with the increase in CIT and the DGF rate, no increase in the incidence of AR or any impact on the renal graft function was observed in up to one year follow-up, suggesting that, even without reducing the risk of DGF, the use of thymoglobulin may be associated with protection from the late effects of IRI on the renal graft (20) . Although many clinical trials demonstrated that immunological induction with thymoglobulin is safe and effective (12)(13)(14)(15)(16) , the best regimen with regard to number of doses, frequency and accumulated antibody dose has not been established yet. A great part of the experience with the use of antibodies in kidney transplantation was acquired by its use for the treatment of AR, which, in some protocols, reached a total of 14 doses.…”
Section: Discussionmentioning
confidence: 99%
“…A great part of the experience with the use of antibodies in kidney transplantation was acquired by its use for the treatment of AR, which, in some protocols, reached a total of 14 doses. Ever since, several studies compared a number of induction protocols, in order to define how many doses or how many days of treatment would be necessary to establish a safety profile for the use of thymoglobulin for immunological induction (13,14) . In this study, in Group 1, a protocol extrapolating from the one indicated for the treatment of AR was used, allowing the use of up to 14 doses, provided the patients remained in DGF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations